Development of a pharmacogenetic-guided warfarin dosing algorithm for Puerto Rican patients. (December 2012) - Ramos, Alga S; Seip, Richard L; Rivera-Miranda, Giselle; Felici-Giovanini, Marcos E; Garcia-Berdecia, Rafael; Alejandro-Cowan, Yirelia; Kocherla, Mohan; Cruz, Iadelisse; Feliu, Juan F; Cadilla, Carmen L; Renta, Jessica Y; Gorowski, Krystyna; et al.
Aim: This study was aimed at developing a pharmacogenetic-driven warfarin-dosing algorithm in 163 admixed Puerto Rican patients on stable warfarin therapy.Patients & methods: A multiple linear-regression analysis was performed using log-transformed effective warfarin dose as the dependent variable, and combining CYP2C9 and VKORC1 genotyping with other relevant nongenetic clinical and demographic factors as independent predictors.Results: The model explained more than two-thirds of the observed variance in the warfarin dose among Puerto Ricans, and also produced significantly better 'ideal dose' estimates than two pharmacogenetic models and clinical algorithms published previously, with the greatest benefit seen in patients ultimately requiring <7 mg/day. We also assessed the clinical validity of the model using an independent validation cohort of 55 Puerto Rican patients from Hartford, CT, USA (R 2 = 51%).Conclusion: Our findings provide the basis for planning prospective pharmacogenetic studies to demonstrate the clinical utility of genotyping warfarin-treated Puerto Rican patients. Original submitted 2 August 2012; Revision submitted 2 October 2012